2023
DOI: 10.7759/cureus.37415
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salivary ABO Blood Group Antigens and Secretor Status in Sriganganagar, Rajasthan: A Correlational Analysis of 300 Samples

Abstract: To estimate the ABO blood groups from saliva samples and to correlate with the secretor status. Materials and methodsA sample size of 300 individuals was selected from the outpatient department of Surendera Dental College & Research Institute, Sriganganagar, India, and from dental camps organized by the college in the near vicinity. Informed consent was obtained from selected individuals to collect their blood and saliva samples. Salivary samples were evaluated for ABO blood groups by the absorption-inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Rajawat et al studied salivary samples in 300 individuals for ABO blood groups by the absorption-inhibition method and found that 250/300 were secretors. They concluded that blood groups could be identified specifically from the saliva of those who were secretors of antigen [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajawat et al studied salivary samples in 300 individuals for ABO blood groups by the absorption-inhibition method and found that 250/300 were secretors. They concluded that blood groups could be identified specifically from the saliva of those who were secretors of antigen [18].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of antigenicity as the time period increased may be due to drying of the tissue, loss of antigens of pulp, inadequate pulp for the experiment, calcification, lysis of the pulp cells, putrefaction of the bodies in an actual forensic scenario, and bacterial contamination [18], and also aerobic gram-negative bacteria grew over a storage period and there is a possibility of some mistyping of blood groups. Some negative results may also be due to processing errors [11,14,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that group B has a higher secretor frequency than group AB, consistent with findings in Karachi, Pakistan (79.5% vs. 45.5%) [ 7 ], and Korea (73.3% vs. 63.6%) [ 11 ]. Other previous reports for groups A, B, AB, and O show varying frequencies: 72.1%, 73.3%, 63.6%, and 86.7% in Korea [ 11 ]; 70.1%, 67.8%, 67.9%, and 88.3% in Iraq [ 12 ]; and 87.1%, 73.3%, 94.2%, and 85.0% in Rajasthan, India [ 13 ], respectively. However, this does not fully explain why group A plasma was not as effective in reducing ABO antibody titers as group B plasma, despite the similar frequency of Le b positivity between groups A and B in Korea.…”
mentioning
confidence: 90%
“…Antigens belonging to the ABO blood group are found on red blood cells, epithelial cells in the digestive and respiratory tracts, and endothelial cells beneath blood arteries, which are capable of producing ABH carbohydrate structures [25]. ABO blood grouping studies have been identified in the dental pulp tissue and secretor status was also noted in salivary samples [26,27]. The S protein of virions produced by individuals of type A may be adorned with A carbohydrate epitopes, while those produced by type B individuals could display B carbohydrate epitopes.…”
Section: Batool Et Al Storry Et Al and Cheng Et Al Examined The Corre...mentioning
confidence: 99%